Hydrodynamics optimization in butterfly swimming: position, drag coefficient and performance - Taiar, R.; Sagnes, P.; Henry, C.; Dufour, A. B.; Rouard, A. H. (Journal of Biomechanics, 1999)
A kinematic study allowed to define the three most propulsive positions during a butterfly swimming cycle, which were: the end of the external sweep, the end of the internal sweep and the end of thrust. These instantaneous positions were different for the ex-world champion Pankratov when compared to another swimmer. Using manikins and a drag-measuring device, we showed that the end of the internal sweep induced the highest drag values and that Pankratov may reduce energy expenditure by taking up a particular position during the end of the swimming cycle. These results point out the relations between swimming movements, passive drag and swimmers' performance.